EU support to civil society organizations in conflict-ridden countries: A governance perspective from Bosnia and Herzegovina, Cyprus and Georgia. Issue 2 (14th March 2016) - Lidén, Kristoffer; Mikhelidze, Nona; Stavrevska, Elena B.; Vogel, Birte
ABSTRACT: From a peacebuilding perspective, EU support for civil society organizations (CSOs) in conflict-ridden countries can be criticized for artificially boosting a liberal, 'bourgeois' civil society at the expense of more representative initiatives at the grassroots level. Seen from a governance perspective, however, this criticism is lacking in nuance and conceals the actual rationale and effects of the support. To advance a realistic debate on international peacebuilding as a form of governance, this article investigates what the character and effects of EU support for CSOs in conflict-ridden countries actually are: how does it affect the relations between the supported organizations and (1) the wider society, (2) the state and (3) between the recipient country and the EU? We consider four ideal types of EU conflict governance: 'liberal peace', 'hollow hegemony', 'vibrant hegemony' and 'post-liberal peace' and compare them to empirical data from Bosnia and Herzegovina, Cyprus and Georgia. We find that while the objectives of promoting peace and democracy through CSO support tend to fail, the strategic interests of the EU are still maintained.